Leadership At The Apex : Politicians and Administrators in Western Local Governments - Mouritzen, Poul Erik.; Svara, James H.; Project Muse. (Pittsburgh : University of Pittsburgh Press, 2002)
Although the relationship between elected officials and appointed executives has often been viewed as a struggle between master and servant-with disagreements as to which group occupies which rol-the authors reveal more interdependence and shared influence than conflict over control.
Studying Institutions and Leadership Comparatively -- Politicians and Administrators in the Political Process: The Theoretical Issues -- Institutions, National Cultures, and Political Leadership -- CEOs' Interactions with Their Political Environment / Marcel van Dam, Geert Neelen -- The CEO's Activities and Role in Policy Making -- CEOs as Political Advisors to Elected Officials -- The Ideal Politician -- The Influence of Local Government Officials -- Partnerships at the Apex of Local Government.
Description based on print version record.
JSTOR
Keywords: Municipal government; Leadership; Municipal officials and employees; Leadership; Administration municipale; Leadership; Fonctionnaires municipaux; municipal government; 88.13 local government bodies; POLITICAL SCIENCE / General; Municipal officials and employees; Municipal government; Leadership; Leiderschap; Lokaal bestuur